Synthesis of cocoa butter substitutes from Cinnamomum camphora seed oil and fully hydrogenated palm oil by enzymatic interesterification - Ma, Xiaoyu (J Food Sci Technol, 2019)
Cinnamomum camphora trees have a vast range of distribution in southern China and the seed oil has unique fatty acid (FA) properties and various bio-activities. In this work, Cinnamomum camphora seed oil (CCSO) was utilized to synthesize value-added cocoa butter substitute (CBS) by enzymatic interesterification. The synthesis was conducted in a solvent-free system by blending CCSO with fully hydrogenated palm oil under the catalysis of Lipozyme RM IM. The reacted products were assessed with physicochemical properties, i.e. FA composition, slip melting point (SMP), triacylglycerol (TAG), crystal polymorphism, microstructure, melting and crystallization properties and solid fat content (SFC). It showed that MCFAs (capric acid plus lauric acid) was the main fatty acid in products, accounting for over 45%. Comparing to physical blends, some novel TAG species such as LaLaLa and LaMLa/LaLaM were observed after enzymatic interesterification whereas SSS TAGs were reduced. IP presented a ball-like, well-distributed and nearly round crystal microstructure and a smaller crystal size. Moreover, it should be mentioned that SFC of IP ranging from 31.85 to 38.47% at 25 °C with most β′ crystal forms, was beneficial to improve the spreadability in term of confectionery products and baked goods. The SMP of the interesterified products was 35.75–36.15 °C which closed to the commercial CBS. Hence, the products synthesized can be used to as CBS, and the results in this study also showed CCSO have value-added applications.